PENINGKATAN PENGETAHUAN DAN SIKAP KELUARGA PASIEN STROKE MELALU VIDEO MIRROR THERAPY: PROMOSI KESEHATAN BERBASIS SELF CARE - Sodikin, Sodikin (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2025)
Mirror therapy videos have proven to be an effective health education medium for improving the knowledge and attitudes of stroke patients' families regarding home-based care. This study aims to evaluate the extent to which mirror therapy videos, compared to pamphlets, influence the understanding and attitudes of families toward stroke care. The research used a quasi-experimental design with two groups, each consisting of 15 respondents: one group received education through mirror therapy videos, while the other received pamphlets. Data were collected using questionnaires and analyzed using an independent sample t-test. The results showed that the video group had a higher average knowledge score (10.13) and attitude score (31.33) compared to the pamphlet group (knowledge: 8.80, attitude: 29.27). Statistical tests revealed significant differences between the two groups, with p-values of 0.044 for knowledge and 0.047 for attitude (p < 0.05). This study concludes that mirror therapy videos are more effective than pamphlets in enhancing the knowledge and attitudes of stroke patients' families, and are therefore recommended as a primary educational medium for home stroke care.